Language as a Medium for Nature Conservation: Revitalization of Madura’s Flora-Fauna Lexicon within the Framework of Indigenous Knowledge - Khusnul Khotimah; Arief Setyawan; Mulyono (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study examines efforts to revitalize the lexicon of flora and fauna in the Madurese language as a form of both linguistic preservation and safeguarding of endangered indigenous ecological wisdom. Employing ecolinguistic and linguistic ethnographic approaches, the research analyzes natural lexicons that are disappearing due to language shift, modernization, and environmental degradation. Data were collected through in-depth interviews with native speakers, analysis of traditional documents (folklore, mantras, and proverbs), and participatory observation in Madurese communities. The findings reveal that: (1) Madurese flora-fauna lexicons embody complex ecological concepts, such as medicinal plant classifications and wildlife knowledge systems; (2) The threat of lexicon extinction is driven by sociolinguistic factors (dominance of Indonesian) and ecological pressures (land-use changes); (3) Effective revitalization strategies include integration into local-content education, digital documentation, and reinforcement of environmentally rooted customary practices. The study concludes that preserving Madurese natural lexicons is not merely a linguistic concern but also a critical resistance to socio-ecological crises. These findings recommend an interdisciplinary approach combining linguistics and political ecology to restore the relationship between language, indigenous knowledge, and environmental sustainability.